(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2019)
The classification of the main seasonal heat energy storage batteries is given, and the modern circuit diagram of the phase shift battery as part of the system with a heat pump and a solar collector is considered. The disadvantage of water heaters is their large volume in most cases. By utilizing the accumulated latent heat of substances, a significant reduction in capital costs is achieved. The possibility of creating energy-saving ventilation systems with the use of a seasonal heat accumulator working on phase transformations of heat-accumulating material is considered. The linear stationary mathematical model of the battery thermal balance is made and on the basis of the calculation results graphs and diagrams are constructed enablingto analyze the work of the heat accumulator during the year. The classification of the main seasonal accumulators of thermal energy and ventilation systems with a ground heat exchanger use is considered. In the article the theoretical and computational research of the seasonal heat accumulator creation and application possibility working on phase transitions of heat-accumulating substances (water) in the ventilation system of a residential individual house is given.